2018
DOI: 10.1136/jmedgenet-2018-105606
|View full text |Cite
|
Sign up to set email alerts
|

Screening of BRCA1/2 deep intronic regions by targeted gene sequencing identifies the first germline BRCA1 variant causing pseudoexon activation in a patient with breast/ovarian cancer

Abstract: BackgroundGenetic analysis of BRCA1 and BRCA2 for the diagnosis of hereditary breast and ovarian cancer (HBOC) is commonly restricted to coding regions and exon-intron boundaries. Although germline pathogenic variants in these regions explain about ~20% of HBOC cases, there is still an important fraction that remains undiagnosed. We have screened BRCA1/2 deep intronic regions to identify potential spliceogenic variants that could explain part of the missing HBOC susceptibility.MethodsWe analysed BRCA1/2 deep i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…9 Thus, a substantial proportion of patients currently receiving DNA testing are likely to benefit from the addition of RNA genetic testing. Several studies have also identified pathogenic deep-intronic variants across a range of hereditary cancer conditions, including hereditary breast and ovarian cancer (HBOC), 10,11 Lynch syndrome, 12,13 familial adenomatous polyposis, 14 neurofibromatosis, 15 and Li-Fraumeni syndrome. 16 However, the prevalence of cancer-predisposing deep-intronic variants has not been fully explored due to the limited scalability of previous RNA testing methods.…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus, a substantial proportion of patients currently receiving DNA testing are likely to benefit from the addition of RNA genetic testing. Several studies have also identified pathogenic deep-intronic variants across a range of hereditary cancer conditions, including hereditary breast and ovarian cancer (HBOC), 10,11 Lynch syndrome, 12,13 familial adenomatous polyposis, 14 neurofibromatosis, 15 and Li-Fraumeni syndrome. 16 However, the prevalence of cancer-predisposing deep-intronic variants has not been fully explored due to the limited scalability of previous RNA testing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, human BRCA2 variants in mESCs rendered similar mRNA transcript profiles as previously detected in LCLs and minigene analysis with all major aberrant splicing events identified. 12 , 28 31 The complementation phenotype of two variants, c.316+5G>C and c.7007G>A, resembled that of high-risk (class 4/5) variants with respect to their inability to rescue the cell lethality imposed by Cre-mediated loss of mBrca2 (Fig. S2 ).…”
Section: Resultsmentioning
confidence: 94%
“…Also, deep intronic variants can impose aberrant splicing as previously reported for c.6937+594T>G. 28 , 31 Due to the activation of a cryptic splice site an intronic fragment of 95 bases is inserted between exons 12 and 13 leading to an out-of-frame transcript. Molecular analysis revealed that although intron retention seems to be the predominant splicing event (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Whilst this represents a significant improvement to molecular diagnostic services, we expect that the true impact of such analysis strategies will be more pronounced. The targeted NGS approaches employed within this large cohort ignore deeply intronic regions of genes, and as shown here (Box 1, Case Example) and in other studies, [43][44][45][46][47] variation within these regions can cause aberrant splicing through the production of novel cryptic exons. We expect, therefore, that extending variant prioritization approaches to large cohorts of individuals with whole genome sequencing datasets will enable the identification of clinically relevant deeply intronic variants.…”
Section: Significant Impact Of Incorporating Spliceai Scores Into Roumentioning
confidence: 78%